PENGARUH SISTEM REKRUTMEN TERHADAP KINERJA KARYAWAN PT. PERMATA INDO SEJAHTERA MEDAN - Nurbeti Nurbeti; Hotli Naibaho (JURNAL REGIONOMIC, 2021)
This research was conducted at PT.Permata Indo Sejahtera Medan Branch, with the aimof knowing the effect of the recruitment system on employee performance. The datacollection technique used was by distributing questionnaires, the sample in this study was95 people. Analysis of the data used is quantitative analysis with a simple linearregression method and processed using the SPSS 22 program. Based on the results of thestudy, it is obtained partially the Recruitment System (X), t count is equal to (2.523 ) > ttable (1.665) and significance value (Sig .) 0.00 < 0.05. It is concluded that theRecruitment System has a significant effect on employee performance. The R-squarevalue indicates that the 0.717 independent variable Recruitment System (X) is able toexplain 51% of the data variance on the Performance variable (Y). The rest, as much as49% of the variance of the data on Performance is explained by other variables notexamined in this model. PT. Permata Indo Sejahtera Medan is expected to be able torecruit qualified employees in accordance with the recruitment system regulations thathave been implemented to support employee performance towards a better direction.